2017
DOI: 10.1111/edt.12334
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic dental injuries in children with special health care needs

Abstract: Prevalence of TDI was higher in CSHCN, and associated with increased overjet and incompetent lips. Uncomplicated crown fracture was the most common injury. In both groups, the main reason for not seeking treatment was lack of dental awareness among parents/caregivers; however, difficulties in getting an appointment and availability of dental clinics willing to see children were more prominent in the CSHCN group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 20 publications
1
57
0
4
Order By: Relevance
“…Al Sarheed did not statistically compare patients with and without SN with respect to TDI. Although most studies found that the prevalence of dental trauma was higher in the case group than the control group, only two studies found that the difference was statistically significant . Other studies have shown a higher prevalence of trauma in healthy patients when compared to patients with special needs …”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Al Sarheed did not statistically compare patients with and without SN with respect to TDI. Although most studies found that the prevalence of dental trauma was higher in the case group than the control group, only two studies found that the difference was statistically significant . Other studies have shown a higher prevalence of trauma in healthy patients when compared to patients with special needs …”
Section: Resultsmentioning
confidence: 93%
“…In the study sample representative section, some studies showed major problems for the source of sample and minor problems in sampling method . No problems in sample size were found in six studies, and some studies showed major problems in entry criteria's/exclusions …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…An adequate labial closure is a protective factor. 24 It is important to determine if parents and/or caregivers of children with CP are aware that labial incompetence makes the patient prone to further damage in case of suffering oral trauma. Knowing how to identify this type of condition will improve the referral time to orofacial motor therapy.…”
Section: Discussionmentioning
confidence: 99%